Failure Mode and Effect Analysis (FMEA) for Improving the Efficiency of a Two Combustion Chamber Downdraft Gasification Stove - Suryaman; Zakaria, Kiki; Yuningsih, Siti Hadiaty (Operations Research: International Conference Series, 2025)
The growing energy demand in areas lacking access to modern infrastructure drives the development of biomass-based thermal technologies, such as the dual-chamber downdraft gasification stove. This stove offers higher efficiency and lower emissions compared to direct combustion but still poses failure risks in various system components. This study aims to identify critical failure modes affecting the thermal efficiency of the stove through the Failure Mode and Effect Analysis (FMEA) approach. The analysis involved mapping the system's structure and functions, followed by evaluating failure modes using three parameters: Severity (S), Occurrence (O), and Detection (D) to obtain the Risk Priority Number (RPN). Results indicate the highest risk occurs in the combustion system (RPN 180), followed by the air control system (RPN 160). Key causes include suboptimal secondary air distribution and valve blockage. Other systems such as insulation, maintenance access, safety, and fabrication had lower RPNs but still require design and quality control improvements. Recommendations focus on improving airflow design, using high-temperature-resistant materials, and adopting precision fabrication procedures. Using the FMEA approach, the gasification stove can be enhanced in terms of reliability, efficiency, and user safety, making it more feasible as a small-scale renewable energy solution for communities.